PENGARUH IKLAN TERHADAP KEPUTUSAN MEMILIH UIN ALAUDDIN MAKASSAR - Haruna, Rahmawati (Komodifikasi, 2018)
Today, the awareness to use mass media in building its image among universities is increasingly visible. This is triggered by the increasingly intense competition for new students, including the State Islamic University (UIN) Alauddin Makassar. Based on the results of research, it was found that the friend is the main or dominant information source used by new students to obtain information about uin Alauddin Makassar. Other media such as billboards and brochures are also used although relatively small. In addition the family is also a source of information for prospective freshmen. A strong factor of personal interest is the most dominant factor influencing the respondent's decision in choosing UIN Alauddin Makassar as a place of lecture.